2020
DOI: 10.1186/s13075-020-02218-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-32 in systemic sclerosis, a potential new biomarker for pulmonary arterial hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a severe complication of systemic sclerosis (SSc), associated with a progressive elevation in pulmonary vascular resistance and subsequent right heart failure and death. Due to unspecific symptoms, the diagnosis of PAH is often delayed. On this basis, it is of great value to improve current diagnostic methods and develop new strategies for evaluating patients with suspected PAH. Interleukin-32 (IL-32) is a proinflammatory cytokine expressed in damaged vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…PDGF‐plasma levels have been found to significantly increase in patients with systemic SSc 38 . PAH is a serious complication of SSc, and is accompanied with increased expression of proinflammatory cytokine such as IL‐32 39 . Blocking of the PDGF‐BB/PDGFR‐β signaling pathway reversed the vascular remodeling in an experimental PAH model system 14 .…”
Section: Discussionmentioning
confidence: 99%
“…PDGF‐plasma levels have been found to significantly increase in patients with systemic SSc 38 . PAH is a serious complication of SSc, and is accompanied with increased expression of proinflammatory cytokine such as IL‐32 39 . Blocking of the PDGF‐BB/PDGFR‐β signaling pathway reversed the vascular remodeling in an experimental PAH model system 14 .…”
Section: Discussionmentioning
confidence: 99%
“…[37] Cells from patient-samples also differentially express pro-inflammatory cytokines such IL-32, IL-26, IL-16, which are up-regulated in the serum and in the lesional skin of SSc patients. [38][39][40] These cytokines have been implicated in the pathogenesis of other inflammatory skin diseases [41][42][43][44] by promoting secretion of other inflammatory cytokines (TNFa, IL6) and chemokines (IL8, CXCL2) by macrophages and by acting as chemoattractants and modulators of T-cell activation. Single-cell trajectory analysis indicates that SSc CD4 + and CD8 + T RM cells are distributed throughout pseudotime, while SSc T MM are mostly found in late pseudotime, indicating distinct gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…ECs lining injuries are the early events occurring in patients with SSc [152,153]. In these patients, arteries are generally impaired and characterized by intimal hyperplasia, medial thickening, obliteration of the lumen and inflammation [58,154], thus contributing to the vascular remodelling occurring during PAH [155]. It has been reported that EndMT may also play a pivotal role during the PAH pathogenesis, promoting dysfunction of the ECs [156].…”
Section: Evidence Of Endmt During Human Sscmentioning
confidence: 99%